Argentina: la Orden de San Agustín desde la Reforma Carolina hasta nuestros días (Archivo Agustiniano, 2023)
There are several reforms that the Order of St. Augustine has undergone in the Río de la Plata (current Argentina), but if we analyze the results there are serious doubts about the real intentions that drove them.We make this statement because it is still true that "by their fruits you will know them", and these in the alleged reforms are very different, because the criteria applied in each of them are different, which already offers a good point of support to get their corresponding interpretations.
Keywords: 19th Century; 20th Century; 18th Century; Carolina Reform; Argentina; Augustinian monastery of St John (Argentina); Augustinian Monatery of Mendoza (Argentina); Muzi mission; Regalism; Liberalism; Augustinian Order